Metal-Free Transamidation of Secondary Amides by N-C Cleavage - Rahman, Md. Mahbubur; Li, Guangchen; Szostak, Michal (Journal of organic chemistry, 2019)
Transamidation reactions represent a fundamental chemical process involving conversion of one amide functional group into another. Herein, we report a facile, highly chemoselective method for transamidation of N-tert-butoxycarbonylation (N-Boc) activated secondary amides that proceeds under exceedingly mild conditions in the absence of any additives. Because this reaction is performed in the absence of metals, oxidants, or reductants, the reaction tolerates a large number of useful functionalities. The reaction is compatible with diverse amides and nucleophilic amines, affording the transamidation products in excellent yields through direct nucleophilic addition to the amide bond. The utility of this methodology is highlighted in the synthesis of Tigan, a commercial antiemetic, directly from the amide bond. We expect that this new metal-free transamidation will have broad implications for the development of new transformations involving direct nucleophilic addition to the amide bond as a key step.